2021
DOI: 10.1177/13623613211043643
|View full text |Cite
|
Sign up to set email alerts
|

Short report: Call to action for autism clinicians in response to anti-Black racism

Abstract: Anti-Black racism is a pervasive issue in the autism field that affects the autism service pathway, which ranges from identification of concerns to ongoing service navigation. In this short report, we provide a working model of the autism service pathway and highlight ways in which anti-Black racism affects all components of the pathway. We summarize the literature that demonstrates the effects of racism within autism assessment, treatment, and quality of care. We end with six recommendations for systemic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Implicit racial biases pervade health service systems in the United States and the autism service system is no exception (Straiton & Sridhar, 2021). For autism-related care, Black families have reported that clinicians often dismissed the family's concerns about their child's development and attributed them to poor parenting and challenging behavior instead of autism, leading to lower quality or fewer services (Stahmer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Implicit racial biases pervade health service systems in the United States and the autism service system is no exception (Straiton & Sridhar, 2021). For autism-related care, Black families have reported that clinicians often dismissed the family's concerns about their child's development and attributed them to poor parenting and challenging behavior instead of autism, leading to lower quality or fewer services (Stahmer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a social determinant of health issue is community‐level adversity, such as being bullied, living in foster care, or witnessing violence; these experiences can lead to mental and behavioral health challenges among children (Pachter et al., 2017). Even with added context, the finding raises questions related to racism in assessment and evaluation practices (Straiton & Dridhar, 2021). But it also brings up issues of cultural relevance of the assessment tools that are used by providers.…”
Section: Discussionmentioning
confidence: 95%
“…Future research on child maltreatment among autistic youth should include consideration of caregiver and family trauma, in order to better understand the consequences of caregiver trauma for youth as well as why caregiver trauma and child maltreatment are linked across generations. It will be essential for research to actively prioritize the inclusion, prioritization, and affirmation of racially, ethnically, and socioeconomically diverse communities in autism research, in consultation and collaboration with diverse autistic communities (see Maye et al, 2021 andStraiton &Sridhar, 2021 for urgently and immediately needed actions for enhancing equity in autism research).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%